2019
DOI: 10.3390/cancers11111754
|View full text |Cite
|
Sign up to set email alerts
|

The mRNA-binding Protein TTP/ZFP36 in Hepatocarcinogenesis and Hepatocellular Carcinoma

Abstract: Hepatic lipid deposition and inflammation represent risk factors for hepatocellular carcinoma (HCC). The mRNA-binding protein tristetraprolin (TTP, gene name ZFP36) has been suggested as a tumor suppressor in several malignancies, but it increases insulin resistance. The aim of this study was to elucidate the role of TTP in hepatocarcinogenesis and HCC progression. Employing liver-specific TTP-knockout (lsTtp-KO) mice in the diethylnitrosamine (DEN) hepatocarcinogenesis model, we observed a significantly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 74 publications
1
35
0
Order By: Relevance
“…These authors suggested that ZFP36 downregulation is inversely correlated to the Wnt/β-catenin pathway, which is constitutively activated in CRC, and that there is a loss of posttranscriptional regulatory circuits during tumor development and progression. Coincidently, a recent study also found that overexpressed ZFP36 could decrease EMT and colony formation in vitro , and promote chemosensitivity to doxorubicin or sorafenib (Krohler et al, 2019 ), which further suggested the positive role of ZFP36 in upregulating chemosensitivity of HCC cells. Our work indicated that PRC1 expression is controlled by ZFP36 through ARE-mediated post-translational regulation.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…These authors suggested that ZFP36 downregulation is inversely correlated to the Wnt/β-catenin pathway, which is constitutively activated in CRC, and that there is a loss of posttranscriptional regulatory circuits during tumor development and progression. Coincidently, a recent study also found that overexpressed ZFP36 could decrease EMT and colony formation in vitro , and promote chemosensitivity to doxorubicin or sorafenib (Krohler et al, 2019 ), which further suggested the positive role of ZFP36 in upregulating chemosensitivity of HCC cells. Our work indicated that PRC1 expression is controlled by ZFP36 through ARE-mediated post-translational regulation.…”
Section: Discussionmentioning
confidence: 82%
“…Several publications have demonstrated that ZFP36 is linked to cancer thanks to evidence showing its down-regulated state in several tumors (Sanduja et al, 2012 ; Griseri and Pages, 2014 ; Montorsi et al, 2016 ). Interestingly, a very recent paper discovered that ZFP36 deletion could exert anti-tumorigenicity actions due to effects on inflammation and metabolism in a diethylnitrosamine (DEN) hepatocarcinogenesis model (Krohler et al, 2019 ). But during hepatic tumor progression, ZFP36 acted as tumor-suppressor by inhibiting cell proliferation and migration, and slightly increasing chemosensitivity to doxorubicin and sorafénib (Krohler et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NOTCH1 Thymocyte-specific ZFP36L1 and ZFP36L2 deficient mice develop T cell acute lymphoblastic leukemia by upregulating Notch 1 [8]. TTP is downregulated in HCC tumors and hepatic TTP has a tumor suppressive role during tumor progression [54].…”
Section: Zfp36l1mentioning
confidence: 99%
“…TTP is significantly downregulated in liver tumors. During tumor progression, TTP functions as a tumor suppressor and inhibits proliferation and migration, reduces expression of several oncogenes, and increases chemo sensitivity [54]. The anti-proliferative properties of metformin, an anti-diabetic drug, in breast cancer cells were mediated by induction of TTP through c-Myc downregulation [28].…”
Section: Ttp Family Proteins and Tumor Suppressor And Oncogenic Rolesmentioning
confidence: 99%